Pengaruh Pemasaran Digital, Kualitas Produk, Promosi, Citra Merek Dan Kepercayaan Terhadap Keputusan Pembelian Lipstik Wardah - Syahara Deliana Adhiestya; Sutarmin . (CV. ITTC INDONESIA, 2024)
Nowadays, business competition brings many opportunities and challenges for entrepreneurs, especially businesses in the cosmetics sector. One of the cosmetic products that is often used by Indonesians is Wardah products. This study is to analyze the effect of digital marketing, product quality, promotion, brand image and trust on Wardah lipstick purchasing decisions. The data used in the study are primary data obtained by distributing questionnaires to respondents. The sample in this study were 97 respondents with sampling using non probability sampling with accidental sampling method. Data analysis using multiple linear regression analysis with the help of SPSS v.26. Based on the results of this study, it shows that digital marketing, product quality, promotion, brand image and trust have a positive effect on Wardah lipstick purchasing decisions.